Effectiveness of Using Soft Exosuit in Stroke Case to Improve Walking Speed And Endurance - Pratama, Aditya Denny; Widyadhana, Rakha Shidqi (Jurnal Fisioterapi Terapan Indonesia, 2024)
Stroke is a clinically defined syndrome of acute, focal nerve discharge caused by vascular injury (infarction, hemorrhage) of the central nervous system. Punches can cause damage to the brain and affect a person's ability to walk, balance and coordinate movements. Impaired gait is common in stroke cases, often resulting in poor recovery of mobility and inability to carry out daily activities without assistance. One of the interventions that can be used is a soft exosuit. This method can help overcome walking problems in stroke patients where soft exosuits are used to increase walking speed and walking endurance. The purpose of this study was to determine the effectiveness of giving a soft exosuit to stroke patients to improve gait speed and gait endurance This research is a literature review study in narrative form, in which 6 articles were found that were reviewed after searching and searching four databases. The results of the review found that 40 patients with a 6MWT score of 0.5 m/s aged >55 years were given intervention in the form of exo gait training with a frequency of 5 times/week. After 8 weeks of intervention, evaluation data analysis found an increase in walking speed in stroke patients. Based on the results of this review, it can be interpreted that the soft exosuit provides a physiological effect that is in accordance with the stroke conditions of patients with walking disorders so that it can be used as an additional intervention option to improve speed and gait endurance.